PENGARUH PENAMBAHAN TEPUNG DAUN JATI DALAM PAKAN TERHADAP PENAMPILAN PRODUKSI DAN WARNA KUNING TELUR AYAM PETELUR - Edi, Didik Nur; Natsir, M. Halim (BUANA SAINS, 2024)
This study aimed to assess the impact of dietary teak leaf powder on the egg color and productivity of laying hens. A total of 240 30-week-old laying hens were divided into six treatments, each of which had four replications (10 birds each). The treatments used control were AV (0.05% antibiotic virginiamycin) and (no feed additive), P1: 0.4% teak leaves powder, P2: 0.8% teak leaves powder, P3: 1.2% teak leaves powder, and P4: 1.6% teak leaves powder. The result indicated that the treatments had a highly significant (P0.01) impact on hen day productivity (HDP), egg mass, and feed conversion ratio (FCR) but had no effect (P0.05) on feed intake, egg weight, or yolk color. When AV was used instead of the control, HDP, egg mass, and FCR improved (P0.01). The treatment P2, P3, and P4 had a better HDP, egg mass, and FCR (P0.01) than the control. Laying hens fed AV had a higher HDP (P0.01) than those fed teak leaves powder (P1, P2, P3, and P4), however, the use of P3 and P4 had equal results as AV in terms of egg mass and FCR. The teak leaves powder at the level of 1.2% is effective in substituting commercial antibiotics.